PERSONAL HYGIENE PADA SISWA/SISWI KELAS IV DAN V DI SD SWASTA KARYA BAKTI HELVETIA KECAMATAN SUNGGAL KABUPATEN DELI SERDANG Personal Hygiene on Students in Grade IV and V at SD Swasta Karya Bakti Helvetia Sunggal District Deli Serdang Regency - Neni Ekowati Januariana; Rosdiana Rosdiana; Ulfa Mawadda (Jurnal Kesehatan dan Fisioterapi, 2022)
Background: Personal hygiene is done to maintain the cleanliness and health of one both physically and mentally. Personal hygiene is the first step in realizing the health because the body clean to minimize the risk of a person infected with a disease, especially diseases associated with personal hygiene bad.Purpose :To to look at the relationship between knowledge, attitudes and parenting parents on personal hygiene.Method : The research method is an analytic survey with a cross-sectional approach. The population was 103 students using a total population of 103 students. The research instrument used a questionnaire. The analysis used univariate and bivariate analysis with chi square statistical test.Result :Itshowed the chi square test showed that there was a relationship between knowledge and personal hygiene, p-value was .003<.05, the relationship between attitude and personal hygiene was .006<.05, there was a relationship between parenting and personal hygiene, p-value was 0.000<.05. Conclusion:There was a relationship between knowledge and personal hygiene, there was a relationship between attitude and personal hygiene and there was a relationship between parenting and personal hygiene. Keywords: Knowledge, Attitude, Parenting, Personal Hygiene.